The influence of occlusion on masticatory performance and satisfaction in complete denture wearers - ÖZKAN, YASEMİN (WILEY, 2013)
Complete dentures should satisfy patients' needs for comfort, function and aesthetics. Thirty edentulous patients were enrolled in this study. Two sets of complete dentures were made for each patient: one with bilaterally balanced occlusion and the other with lingualised occlusion. The patients used each type of denture for 6 months. A single-blind study design was used in which the patients were not aware of the exchange of dentures. In each 3-month period, electromyographic measurements of the anterior temporalis and masseter muscles were performed. At the end of 6 months, patient satisfaction was evaluated. The second measurement of lingualised occlusion showed the greatest muscle activity, while chewing gum in both the anterior temporalis and masseter muscles (174.5 and 208.19 mu V, respectively). The greatest maximum voluntary contraction was also found for the second measurement of lingualised occlusion for both the anterior temporalis and masseter muscles (142.91 and 187.55 mu V, respectively). The mean chewing time decreased with lingualised occlusion. The percent distribution of the patients' ratings of their complete dentures and patient satisfaction with lingualised occlusion were higher than those for bilaterally balanced occlusion. Complete dentures with lingualised occlusion increased masticatory performance, maximum voluntary contraction and patient satisfaction and decreased chewing time.
Keywords: bilateral balanced occlusion; complete denture; electromyography; lingualised occlusion; patient satisfaction; IMPLANT-RETAINED OVERDENTURES; JAW-ELEVATOR MUSCLES; MAXIMUM BITE FORCE; QUALITY-OF-LIFE; LINGUALIZED OCCLUSION; SURFACE EMG; MASSETER MUSCLE; SOFT FOOD; DENTATE; TRIAL